2012
DOI: 10.1371/journal.pone.0045492
|View full text |Cite
|
Sign up to set email alerts
|

Dacarbazine and the Agonistic TRAIL Receptor-2 Antibody Lexatumumab Induce Synergistic Anticancer Effects in Melanoma

Abstract: Mapatumumab and lexatumumab (targeting death receptor 4 (DR4) and 5 (DR5), respectively) are agonistic TRAIL receptor antibodies that induce apoptosis in a wide range of cancer cells. The potency of mapatumumab and lexatumumab was assessed in mono therapy protocols, and the ability to sensitize for dacarbazine (DTIC) treatment was explored in ten different melanoma cell lines. Our data indicated that melanoma cell lines tend to be resistant to mapatumumab, most likely due to low expression of DR4, while a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…In line with what has been observed by others [149], treatment with the TRAIL agonist decreased the viability in both cell lines as a single agent. When combining Lexatumumab with CD437, the cell viability was further reduced and resulted in a synergistic effect.…”
Section: Combinational Treatment and Therapeutic Relevance Of Cd437 Asupporting
confidence: 91%
See 1 more Smart Citation
“…In line with what has been observed by others [149], treatment with the TRAIL agonist decreased the viability in both cell lines as a single agent. When combining Lexatumumab with CD437, the cell viability was further reduced and resulted in a synergistic effect.…”
Section: Combinational Treatment and Therapeutic Relevance Of Cd437 Asupporting
confidence: 91%
“…Combinational therapy represents a potential strategy for treating TRAIL resistant cancers. In line with this, Lexatumumab has shown promising results in preclinical studies of melanoma, in particular in combination with other agents such as Dacarbazine[149] and Anisomycin[150]. Treatment with Lexatumumab is generally well tolerated as assessed in a Clinical phase I trial of pediatric patients with solid tumours[151].…”
mentioning
confidence: 86%
“…Six of the nine validated agents met the prioritization criteria of imparting >20% increased reduction in cell viability over the expected observations and a >25% reduction in absolute cell viability with the combination: azacitidine, bortezomib, dacarbazine, hydroxyurea, sorafenib, and vismodegib (Figure 2C). Synergy between TRAIL and bortezomib, dacarbazine, hydroxyurea, or sorafenib has been previously reported (3, 5, 6). Examining monoagent and combinatorial activity, we found that adding vismodegib to ONC201 did not result in improved activity compared to monoagent ONC201, but rather reversed surprising agonistic growth effects of monoagent vismodegib that we observed in several cell lines.…”
Section: Resultsmentioning
confidence: 75%
“… 126 Like mapatumumab, lexatumumab mediated synergistic effects in combination with chemotherapeutics. 135 In combination with radiation, lexatumumab showed some clinical activity in pediatric solid tumors. 136 …”
Section: Phage Display Derived Antibodies In Clinical Developmentmentioning
confidence: 99%